2016
DOI: 10.1093/mnras/stw1244
|View full text |Cite
|
Sign up to set email alerts
|

Astrometry of mutual approximations between natural satellites. Application to the Galilean moons

Abstract: Typically we can deliver astrometric positions of natural satellites with errors in the 50-150 mas range. Apparent distances from mutual phenomena, have much smaller errors, less than 10 mas. However, this method can only be applied during the equinox of the planets. We developed a method that can provide accurate astrometric data for natural satellites -the mutual approximations. The method can be applied when any two satellites pass close by each other in the apparent sky plane. The fundamental parameter is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 22 publications
(34 reference statements)
1
37
0
Order By: Relevance
“…The updated results for 2009 now agree within 1 with those from Arlot et al (2014a) and from Morgado et al (2016). The internal mean uncertainty was 10.1 mas (∼ 31 km).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The updated results for 2009 now agree within 1 with those from Arlot et al (2014a) and from Morgado et al (2016). The internal mean uncertainty was 10.1 mas (∼ 31 km).…”
Section: Discussionsupporting
confidence: 83%
“…In the last columns, we have the rms between the observed light fluxes and the fitted ones, the number of images utilised ( ) and the normalised 2 of our fit. Morgado et al (2016). Comparison between the different reduction process divided by the uncertainty of each parameter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent attempt is the mutual approximations technique developed by us (Morgado et al 2016), primarily suggested by Arlot et al (1982). In this method, the instant of the maximum apparent approximation in the sky plane between two moving satellites can be determined with a precision that corresponds to less than 10 mas.…”
Section: ;mentioning
confidence: 99%
“…Positions obtained using mutual phenomena have uncertainties at a level of 15-60 km (Saquet et al 2018;Arlot et al 2014;Dias-Oliveira et al 2013;Emelyanov 2009), but they only occur at every equinox of the host planet (every six years in the case of Jupiter). The technique of mutual approximations also provides positions with uncertainties between 15-60 km, and this does not depend on the equinox of Jupiter (see Morgado et al 2016Morgado et al , 2019. Stellar occultation is then the only ground-based technique that can furnish astrometric measurements that are comparable with space probes, which usually have uncertainties smaller than 5 km (Tajeddine et al 2015).…”
Section: Introductionmentioning
confidence: 99%